Growing Up, Hooking Up, and Drinking: A Review of Uncommitted Sexual Behavior and Its Association With Alcohol Use and Related Consequences Among Adolescents and Young Adults in the United States - Garcia, Tracey A.; Litt, Dana M.; Davis, Kelly Cue; Norris, Jeanette; Kaysen, Debra; Lewis, Melissa A. (Frontiers in Psychology, 2019)
Hookups are uncommitted sexual encounters that range from kissing to intercourse and occur between individuals in whom there is no current dating relationship and no expressed or acknowledged expectations of a relationship following the hookup. Research over the last decade has begun to focus on hooking up among adolescents and young adults with significant research demonstrating how alcohol is often involved in hooking up. Given alcohol’s involvement with hooking up behavior, the array of health consequences associated with this relationship, as well as its increasing prevalence from adolescence to young adulthood, it is important to determine the predictors and consequences associated with alcohol-related hooking up. The current review extends prior reviews by adding more recent research, including both qualitative and experimental studies (i.e. expanding to review more diverse methods), research that focuses on the use of technology in alcohol-related hookups (i.e. emerging issues), further develops prevention and intervention potentials and directions, and also offers a broader discussion of hooking up outside of college student populations (i.e., expanding generalization). This article will review the operationalization and ambiguity of the phrase hooking up, the relationship between hooking up and alcohol use at both the global and event levels, predictors of alcohol-related hooking up, and both positive and negative consequences, including sexual victimization, associated with alcohol-related hookups. Throughout, commentary is provided on the methodological issues present in the field, as well as limitations of the existing research. Future directions for research that could significantly advance our understanding of hookups and alcohol use are provided.